Potassium Status and Physicochemical and Mineralogical Properties of Lowland Vertisols in a Rice-Based Cropping System under Tropical Savanna Climate - Ngwe, Kyaw; Kheoruenromne, Irb; Suddhiprakarn, Anchalee (Agriculture and Natural Resources, 2012)
Five proﬁ les of lowland Vertisols—namely, Ban Mi (Bm1, Bm2), Chong Khae (Ck), Lop Buri (Lb) and Wattana (Wa) series— which are typical rice growing soils under tropical savanna climate developed on local alluvium derived from limestone were sampled according to the genetic horizon and studied with the objectives to determine various forms of soil K and to establish the relationships between different forms of K and their soil properties. These soils were slightly alkaline to strongly alkaline and all soils had a clayey texture. Smectite and interstratiﬁ ed kaolinite-smectite dominated their clay fractions with lesser amounts of kaolinite and illite. NH4OAc-exchangeable K of these soils ranged between 19.32 and 130.53 mg kg-1 with an average value of 42.71 mg kg-1. For K fertility status, the topsoil of Bm1 had a “very high” content of available K. The content of available K in the topsoil was observed from high to low in the order Bm1 > Ck > Wa > Lb > Bm2. Non-exchangeable K is potentially available to plants in direct dynamic equilibrium with the exchangeable K form. The non-exchangeable K content of Ck was highest and was lowest in Lb in both the topsoil and subsoil. HNO3-extractable K was very highly signiﬁ cantly correlated with non-exchangeable K (r = 0.995) and signiﬁ cantly correlated with NH4OAc-exchangeable K (r = 0.472) and total K (r = 0.466). The organic matter content was highly signiﬁ cantly correlated with NH4OAcexchangeable K (r = 0.554). Non-exchangeable K was very highly signiﬁ cantly correlated with HNO3 extractable K (r = 0.994) and total K (r = 0.961). The results revealed that different forms of potassium along with organic matter maintenance should be critically considered for management of potassium fertility in these soils for rice-based cropping practice.